A randomised controlled trial to assess the effectiveness and cost of a patient orientated self management approach to chronic inflammatory bowel disease. Issue 11 (11th October 2004) - Kennedy, A P; Nelson, E; Reeves, D; Richardson, G; Roberts, C; Robinson, A; Rogers, A E; Sculpher, M; Thompson, D G
Abstract : Objectives: We developed a patient centred approach to chronic disease self management by providing information designed to promote patient choice. We then conducted a randomised controlled trial of the approach in inflammatory bowel disease (IBD) to assess whether it could alter clinical outcome and affect health service use. Design: A multicentre cluster randomised controlled trial. Setting: The trial was conducted in the outpatient departments of 19 hospitals with randomisation by treatment centre, 10 control sites, and nine intervention sites. For patients at intervention sites, an individual self management plan was negotiated and written information provided. Participants: A total of 700 patients with established inflammatory bowel disease were recruited. Main outcome measures: Main outcome measures recorded at one year were: quality of life, health service resource use, and patient satisfaction. Secondary outcomes included measures of enablement—confidence to cope with the condition. Results: One year following the intervention, self managing patients had made fewer hospital visits (difference −1.04 (95% confidence interval (CI) −1.43 to −0.65); p<0.001) without increase in the number of primary care visits, and quality of life was maintained without evidence of anxiety about the programme. The two groups were similar with respect to satisfaction with consultations. Immediately after the initial consultation, those who had undergone self management training reported greater confidence in being able to cope with their condition (difference 0.90 (95% CI 0.12–1.68); p<0.03). Conclusions: Adoption of this approach for the management of chronic disease such as IBD in the NHS and other managed health care organisations would considerably reduce health provision costs and benefit disease control.